Branch formation in Pulvinularia suecica (Nostocales, Cyanoprokaryota) and considerations on the classification of dichotomously and pseudodichotomously branched genera - Branco, Luis Henrique Z. [UNESP]; Hoffmann, Lucien; Necchi, Orlando [UNESP]; Taboga, Sebastiao Roberto [UNESP]; Moura, Emerson N. M. [UNESP] (Gebruder Borntraeger, 2010)
During a study oil stream macroalgae from highland areas of southeastern Brazil ("Serra do Cipo", Minas Gerais State), populations of Pulvinulario suecica were found. Study of the specimens provided a detailed description of the pseudodichotomous branch formation, in which the bifurcation is originated by one cell that remains at the basis of the branch and does not integrate any of the branch "arms". The taxonomical position of Pulvinularia has been debated since the genus was firstly described. During the course of identification and branch formation studies, it became clear that organisms with dichotomous or pseudodichotomous branching type should be placed under the same family. Thus, it is proposed to adopt Capsosiraceae (sensu Bourrely) to group the genera Capsosira, Colteronema, Desmosiphon, Geitleria, Hyphomorpha, Letestuinema, Loriella, Pulvinularia and Stauromatonema. Additional taxonomical and ecological information on the populations are presented.